2021
DOI: 10.1021/acsenergylett.1c01122
|View full text |Cite
|
Sign up to set email alerts
|

Single Pass CO2 Conversion Exceeding 85% in the Electrosynthesis of Multicarbon Products via Local CO2 Regeneration

Abstract: The carbon dioxide reduction reaction (CO 2 RR) presents the opportunity to consume CO 2 and produce desirable products. However, the alkaline conditions required for productive CO 2 RR result in the bulk of input CO 2 being lost to bicarbonate and carbonate. This loss imposes a 25% limit on the conversion of CO 2 to multicarbon (C 2+ ) products for systems that use anions as the charge carrierand overcoming this limit is a challenge of singular importance to the field. Here, we find that cation exchange memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
281
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(286 citation statements)
references
References 49 publications
5
281
0
Order By: Relevance
“…In the first electrolyzer, we assume Faraday efficiencies of 95% for CO and 5% for hydrogen at a current density of 300 mA/cm 2 and a cell voltage of 2.5 V. Furthermore, we assume a CO 2 conversion of 50%. 95 The small amount of hydrogen is neglected in the process design (i.e., no downstream processing is designed for the separation of hydrogen from CO and unconverted CO 2 ). The CO 2 /CO mixture from the first electrolyzer can in principle directly be fed to the second electrolyzer, but initial experimental results show that the presence of large amounts of CO 2 in the mixture has a detrimental effect on the product distribution.…”
Section: Process Design and Modelingmentioning
confidence: 99%
“…In the first electrolyzer, we assume Faraday efficiencies of 95% for CO and 5% for hydrogen at a current density of 300 mA/cm 2 and a cell voltage of 2.5 V. Furthermore, we assume a CO 2 conversion of 50%. 95 The small amount of hydrogen is neglected in the process design (i.e., no downstream processing is designed for the separation of hydrogen from CO and unconverted CO 2 ). The CO 2 /CO mixture from the first electrolyzer can in principle directly be fed to the second electrolyzer, but initial experimental results show that the presence of large amounts of CO 2 in the mixture has a detrimental effect on the product distribution.…”
Section: Process Design and Modelingmentioning
confidence: 99%
“…For instance, recent work from O’Brien et al demonstrated a CO 2 single pass conversion of 85% using pure water and an IrO 2 catalyst on the anode side with a CEM for proton shuttling. 18 …”
mentioning
confidence: 99%
“… 24 28 Combining these observations with previous BPMEA demonstrations that have traditionally suffered from poor CO 2 reduction selectivities, we hypothesized that the low selectivity in a BPMEA system could be overcome by increasing cation concentrations at the cathode. 17 , 18 , 27 Thus, if the low parasitic CO 2 loss of BPM’s can be achieved simultaneously with improved CO 2 reduction performance, high CO 2 utilization efficiencies would be possible as a result.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2a. Such strategies use acidic environments and bipolar membranes to introduce protons to regenerate carbonate 35,36 or optimize local reaction environments or operating conditions 37,38 . For simplicity of this model, however, our analysis assumes a gas-fed CO2 conversion of 50% with additional steps for product separation and carbonate regeneration processes.…”
Section: Electrolysis Of Molecular Co2mentioning
confidence: 99%